Classification variables of cattle farms in the mountains of León, Spain - Serrano Martínez, E.; Lavín González, P.; Giráldez García, F.J.; Bernués Jal, A.; Bernués Jal, A.; Ruiz Mantecón, A. (Spanish Journal of Agricultural Research, 2004)
This paper reports the f irst stage in the establishment of a farm classif ication system: the identif ication of classification variables. The aim of this work was to identify the variables most appropriate for characterising the cattle farms of the mountains of León, Spain, using multivariate and principal components analysis. The information used was obtained by surveying the cattle farms of the Montaña de Riaño (León) area from 1996-1998. The 35 variables taken into account in the principal components analysis refer to labour, the stock base, production, land use and farm economy. Seven principal components were found to explain 67.1% of the total variance.